The Role of Lymphatic Endothelial Cells in Liver Injury and Tumor Development - Lukacs-Kornek, Veronika (Frontiers in Immunology, 2016)
Lymphatics and lymphatic endothelial cells (LECs) possess multiple immunological functions besides affecting immune cell migration such as inhibiting T cell proliferation and antigen presentation by dendritic cells. Moreover, they control the trans-endothelial transport of multiple molecules and antigens. Emerging evidence suggests their active involvements in immunoregulation, tumor and metastases formation. In the liver, increased lymphangiogenesis, specifically at the portal area has been associated with multiple liver diseases in particular primary biliary cirrhosis, idiopathic portal hypertension, and liver malignancies. Nevertheless, the exact role and contribution of LECs to liver diseases are poorly understood. The review summarizes the current understanding of LECs in liver diseases.